2020
DOI: 10.1038/s41467-020-17644-0
|View full text |Cite|
|
Sign up to set email alerts
|

Immunoprophylactic and immunotherapeutic control of hormone receptor-positive breast cancer

Abstract: Hormone receptor (HR)+ breast cancer (BC) causes most BC-related deaths, calling for improved therapeutic approaches. Despite expectations, immune checkpoint blockers (ICBs) are poorly active in patients with HR+ BC, in part reflecting the lack of preclinical models that recapitulate disease progression in immunocompetent hosts. We demonstrate that mammary tumors driven by medroxyprogesterone acetate (M) and 7,12-dimethylbenz[a]anthracene (D) recapitulate several key features of human luminal B HR+HER2− BC, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
86
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 88 publications
(91 citation statements)
references
References 77 publications
(94 reference statements)
5
86
0
Order By: Relevance
“…Finally, DMBA/ MPA-driven mammary carcinomas resemble human HR + BC in their limited sensitivity to ICBs targeting programmed cell death 1 (PDCD1, best known as PD-1). 4 Intriguingly, we found that DMBA/MPA-driven oncogenesis is not altered by the Rag2 −/genotype (which imposes a defect in T cells and B cells, but largely spares NK cells), nor by the antibody-mediated co-depletion of CD4 + and CD8 + T cells. Conversely, the depletion of cells expressing killer cell lectin like receptor K1 (KLRK1, best known as NKG2D), which encompass NK cells and a fraction of T cells, phenocopied the detrimental effects of the Rag2 −/-Il2rg −/genotype on disease emergence and progression.…”
mentioning
confidence: 56%
See 4 more Smart Citations
“…Finally, DMBA/ MPA-driven mammary carcinomas resemble human HR + BC in their limited sensitivity to ICBs targeting programmed cell death 1 (PDCD1, best known as PD-1). 4 Intriguingly, we found that DMBA/MPA-driven oncogenesis is not altered by the Rag2 −/genotype (which imposes a defect in T cells and B cells, but largely spares NK cells), nor by the antibody-mediated co-depletion of CD4 + and CD8 + T cells. Conversely, the depletion of cells expressing killer cell lectin like receptor K1 (KLRK1, best known as NKG2D), which encompass NK cells and a fraction of T cells, phenocopied the detrimental effects of the Rag2 −/-Il2rg −/genotype on disease emergence and progression.…”
mentioning
confidence: 56%
“…We found that these tumors are histologically and transcriptionally similar to human luminal B (highly proliferative HR + HER2 − ) BC, and emerge by an oncogenic process that depends on the transcriptional activity of estrogen receptor 1 (ESR1) and is coupled to the evasion of immunosurveillance. 4 Consistent with this notion, oncogenesis and tumor progression (culminating in the death of tumor-bearing mice) are accelerated in highly immunodeficient Rag2 −/-Il2rg −/mice (which lack T cells, B cells and NK cells), as well as in mice lacking the key immune effector interferon gamma (IFNG). 4 Moreover, palpable DMBA/MPA-driven mammary carcinomas (1) exhibit a transcriptional signature enriched in genes involved in cell cycle progression and proliferation, but deprived of genes involved in immunological functions, and (2) are scarcely infiltrated by immune effector cells as they display a CD4 compartment that is polarized toward immunosuppression by CD4 + CD25 + FOXP3 + regulatory T (T REG ) cells.…”
mentioning
confidence: 83%
See 3 more Smart Citations